PENERAPAN MODEL PEMBELARAN SENTRA DI TK LABSCHOOL STAI BANI SALEH BEKASI - WATINI, SRI (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
The purpose of this study illustrate the description of the model centers of learning in kindergarten Lab School STAI Saleh Baniare: Psychological Aspects, Child Development, Content or Materials Segi Segi Assessment and LearningThis research method using diskriftif study. The results obtained by the facts of learning centers learning model used in the Lab School Kindergarten STAI Bani Saleh is applied using a combined method of learning centers with the project "Learning By Doing".Keywords: strategy, learning centers, projects